2005
DOI: 10.1021/cm050215d
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth Borates:  One-Dimensional Borate Chains and Nonlinear Optical Properties

Abstract: Three bismuth borates, Bi[B4O6(OH)2]OH (I), BiB2O4F (II), and Bi3[B6O13(OH)] (III), were obtained in boric acid flux at low temperatures and their structures were determined by using single-crystal and powder X-ray diffraction techniques. All these three bismuth borates contain one-dimensional borate chains and crystallize in noncentrosymmetric space groups. I is a hydrated borate, crystallizing in the space group P1 with lattice constants a = 4.300(1) Å, b = 8.587(2) Å, c = 10.518(2) Å, α = 113.11(3)°, β = 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
79
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(82 citation statements)
references
References 24 publications
3
79
0
Order By: Relevance
“…The formation of NBOs expands and weakens the borate structure and consequently lowers T g . We observed that k 0 is approximately constant at 364 nm in the Bi 2 The most interesting result of our UV-visible spectroscopic measurements is the finding of a broad absorption band in the wavelength range of 360-400 nm, just below the optical absorption edge in glasses containing Bi 2 O 3 of 33 mol% and higher. The intensity of this band increases while its center shifts towards longer wavelengths with increase in Bi 2 O 3 concentration (Fig.…”
Section: Uv-visible Absorption Spectroscopysupporting
confidence: 51%
See 2 more Smart Citations
“…The formation of NBOs expands and weakens the borate structure and consequently lowers T g . We observed that k 0 is approximately constant at 364 nm in the Bi 2 The most interesting result of our UV-visible spectroscopic measurements is the finding of a broad absorption band in the wavelength range of 360-400 nm, just below the optical absorption edge in glasses containing Bi 2 O 3 of 33 mol% and higher. The intensity of this band increases while its center shifts towards longer wavelengths with increase in Bi 2 O 3 concentration (Fig.…”
Section: Uv-visible Absorption Spectroscopysupporting
confidence: 51%
“…These glasses have some of the highest densities, refractive indices and coefficients for second and third harmonic generation [1][2][3]. Among several inorganic borate crystals for applications in non-linear optical devices [4], bismuth triborate (BiB 3 O 6 ) phase is known to have the highest coefficient for second harmonic generation [2,[5][6][7]. The coefficients of third harmonic generation also increase with Bi 2 O 3 concentration [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…polyborates, however, are relatively rare, especially for high-valent metal borates. [10][11][12] The small size and high valence imply high local charge accumulation in anhydrous polyborates, which may cause the instability of the structure at high temperature; [13] therefore, it is difficult to synthesize high-valent metal polyborates by conventional solid-state reactions. Recently, remarkable progress has been made in the synthesis of new polyborates by applying improved synthetic routes, such as hydrothermal synthesis [10,11] and boric acid flux methods.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, remarkable progress has been made in the synthesis of new polyborates by applying improved synthetic routes, such as hydrothermal synthesis [10,11] and boric acid flux methods. [12,14] For example, in the Ln 2 O 3 -B 2 O 3 (Ln = rare earth) system, [15] only three kinds of borates, i.e. oxyborate, [16,17] orthoborate [18,19] and metaborate, [20] tions.…”
Section: Introductionmentioning
confidence: 99%